2019
DOI: 10.1177/1559325819825902
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Ketamine Versus Ketamine-Fentanyl-Dexmedetomidine Combination for Anesthesia and Analgesia in Rats

Abstract: Ketamine (KET), a noncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist, is most frequently used as an anesthetic, analgesic, and sedative drug in pediatric clinical practices. However, the adverse effects of KET administration such as psychotic episodes limited the use of KET. The aim of the present study was to evaluate whether the addition of small doses of fentanyl (FENT) and dexmedetomidine would reduce the overall KET consumption without concession on the safety and efficacy of anesthesia and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Successive administration of KFD and PNF led to a lower heart rate during anesthesia, which gradually returned to normal levels after awakening. We observed that the low heart rate of the KFD + PNF group was comparable to that of KFD in our previous study 7 . Moreover, there were no significant changes in the SpO 2 or respiratory rate of the KFD + PNF group during the detection period compared with those of the control.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Successive administration of KFD and PNF led to a lower heart rate during anesthesia, which gradually returned to normal levels after awakening. We observed that the low heart rate of the KFD + PNF group was comparable to that of KFD in our previous study 7 . Moreover, there were no significant changes in the SpO 2 or respiratory rate of the KFD + PNF group during the detection period compared with those of the control.…”
Section: Discussionsupporting
confidence: 80%
“…In a previous study, although we showed that KFD was a safe and effective anesthetic formulation, the duration of the KFD-induced LORR was much longer than that of ketamine alone 7 , which indicated that KFD may not be suitable for short-term surgery. Therefore, reversing anesthesia with antagonists may be a method with a high anesthetic quality and a short duration of anesthesia.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Blood samples were taken at 48 h after STZ administration, under ketamine anesthesia (5 mg/100 g bw, i.p. route) from retro-orbital sinus, followed by rat euthanasia by cervical dislocation [43]. Rats with glucose higher or equal to 200 mg/dL were considered to have diabetes mellitus [20].…”
Section: Experimental Modelmentioning
confidence: 99%